Upaya Peningkatan Pemahaman Tentang Kriteria Ketuntasan Minimal Melalui Pembimbingan Para Guru Di SMPN 212 - Muhamad Ermawan (Universitas Cokroaminoto Yogyakarta, 2022)
This research is to examine the quality of school learning which can be identified by the existence of KKM, where the determination of the Minimum Completeness Criteria (KKM) is the initial stage of implementing the assessment of learning outcomes. The reality in the field of teachers in setting KKM is not based on analysis and does not pay attention to the principles and steps for determining it, therefore it is necessary to have activities at the beginning of the school year that can provide information to teachers which is used as a guide in determining KKM. Therefore, the researchers then conducted a workshop in making KKM. Through the workshop, teachers can improve their ability to determine the Minimum Completeness Criteria (KKM) at SMP Negeri 212 Jakarta for the 2021-2022 academic year. There has been an increase in the readiness of participants in workshop activities at SMP Negeri 212 Jakarta. Besides that, there was also an increase in the ability of teachers to set KKM through school administration in the form of workshops at SMP Negeri 212 South Jakarta which specialized in the scope of supervision of researchers, namely SMP Negeri 212 Jakarta which is in the attachment (attached) from cycle I to cycle I and achieved the target. the minimum that has been set is 85%, meaning that 85% of teachers have been effective in setting the Minimum Completeness Criteria (KKM). Thus it can be concluded that through the Workshop it can improve the ability of teachers to determine the Minimum Completeness Criteria at SMP Negeri 212 Jakarta for the 2021-2022 Academic Year.